If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 5 = 38 Reorder the terms: 5 + -3x = 38 Solving 5 + -3x = 38 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -3x = 38 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 38 + -5 -3x = 38 + -5 Combine like terms: 38 + -5 = 33 -3x = 33 Divide each side by '-3'. x = -11 Simplifying x = -11
| -x+5=38 | | 33.8s=169.0 | | 8r-12=-61+r | | 8.9-3.3j=-2.2j+2.3 | | (4v+1)(9-v)=0 | | 0=x^2-7x+5 | | -25+x=x-25 | | 12.6x-3.7x=160.2 | | 49r^2-16=0 | | u^2-8u+7=0 | | b^2=18-7b | | 8470=x^2+25x+70 | | 3b(10b+7)=0 | | 45x-4(12x-3)=12 | | 3z-23=13+z | | 15+2x=27 | | 3x^2-6=0 | | -3x^2-6=0 | | x^3-3x^2-15x+125= | | 7x-10=6(11x-2x) | | 2(x+3)+3(x+3)=0 | | 7x+2=5x+6 | | 4r+6=8-4r | | -2.3+16=-5q-38 | | -7-7p=3p+23 | | 1.2x+3.7=2.2x-4.5 | | x(x-1)=42 | | 4x-8=6x-12 | | 2x^2-8x+9=0 | | 5(4x-3)=2 | | 5x-12=52 | | 4x^3+16x^2+7x+1=0 |